Game development with Rust and WebAssembly : learn how to run Rust on the web while building a game - Smith, Eric (Packt Publishing, Limited, 2022)
Write an endless runner game for the web in Rust and test, deploy, and debug your 2D game using the WebAssembly toolchain Key Features Build and deploy an endless runner game for the web from scratch through this helpful guide with key images printed in color Learn how to use Rust for web development with WebAssembly Explore modern game development and programming techniques to build 2D games using Rust Book Description The Rust programming language has held the most-loved technology ranking on Stack Overflow for 6 years running, while JavaScript has been the most-used programming language for 9 years straight as it runs on every web browser. Now, thanks to WebAssembly (or Wasm), you can use the language you love on the platform that's everywhere. This book is an easy-to-follow reference to help you develop your own games, teaching you all about game development and how to create an endless runner from scratch. You'll begin by drawing simple graphics in the browser window, and then learn how to move the main character across the screen. You'll also create a game loop, a renderer, and more, all written entirely in Rust. After getting simple shapes onto the screen, you'll scale the challenge by adding sprites, sounds, and user input. As you advance, you'll discover how to implement a procedurally generated world. Finally, you'll learn how to keep your Rust code clean and organized so you can continue to implement new features and deploy your app on the web. By the end of this Rust programming book, you'll build a 2D game in Rust, deploy it to the web, and be confident enough to start building your own games. What you will learn Build and deploy a Rust application to the web using WebAssembly Use wasm-bindgen and the Canvas API to draw real-time graphics Write a game loop and take keyboard input for dynamic action Explore collision detection and create a dynamic character that can jump on and off platforms and fall down holes Manage animations using state machines Generate levels procedurally for an endless runner Load and display sprites and sprite sheets for animations Test, refactor, and keep your code clean and maintainable Who this book is for This game development book is for developers interested in Rust who want to create and deploy 2D games to the web. Game developers looking to build a game on the web platform using WebAssembly without C++ programming or web developers who want to explore WebAssembly along with JavaScript web will also find this book useful. The book will also help Rust developers who want to move from the server side to the client side by familiarizing them with the WebAssembly toolchain. Basic knowledge of Rust programming is assumed.